Nutri-Seed Flakes / Noriham Abdullah … [et al.] - Abdullah, Noriham; Wan Kamarudin, Wan Saidatul Syida; Aziman, Nurain; Zulkifli, Khairusy Syakirah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Nutri-seed flakes is a breakfast cereal prepared from local fruit waste i.e. seed of winter melon fruit as the main ingredient. Food wastes have long been discussed as having potential as functional ingredients. Winter melon fruit is considered as underutilized fruit in Malaysia. Hence, the development of this fruit into more beneficial food product especially the seed part which is considered as waste, is a great challenge. Seed of winter melon is rich in fiber, amino acid, natural sugar, organic acid and phenolic compounds. This invention is to introduce a new type of breakfast cereal using cheap and simple drying method that will not only meet consumers demand but also carries beneficial health properties. Nutri-seed flakes is a tasty and nutritious breakfast cereal using local fruit that can be commercialized and consumed by people of all age groups.